Effect of Vermicompost and NPK Nitrophonska 15:15:15 on the growth and yield of Mung Beans (Vigna Radiata L.) - Intani, Hana; Nurrohim, Muhammad Risky; Faqih, Achmad (International Journal Labs, 2024)
The aim of this research was to determine the effect of combining vermicompost and NPK Nitrophonska 15:15:15 fertilizer on the growth and yield of mung beans (Vigna radiata L.). The research was carried out in May - July 2024 in Pancalang Village, Pancalan District, Kuningan Regency, West Java Province. The research method used was an experimental method using a Randomized Group Design (RAK). The main observations included plant height, number of trifoliate leaves (three leaflets), root length, root volume, root nodules, numbers of pods per plant, and seed weight per plot. The results showed that the combination of VermiCompost fertilizer (K1N2) and Nitrophonka NPK (K2N2) had a significant effect on plant height at 21.28 DAP and 32 DAP, respectively. The K2N2 treatment produced the best plant height (45.87 cm). The number of plant leaves was positively correlated with the number of leaflets on green bean plants (r = 0.466, p 0.05). The K1N2 treatments had the best results from several observation parameters, especially in the weight of seeds per plot in the treatment (4 kg vermisp. and 40 gr NPK).